Deciding discipline, course and university through TOPSIS. Issue 12 (1st December 2020) - Nanayakkara, Chiharu; Yeoh, William; Lee, Alvin; Moayedikia, Alireza
ABSTRACT: During course selection, students have to consider many criteria to arrive at the best course to study at the institution that provides the best fit for their aspirations. However, a central issue that reduces the clarity of course consideration and results in suboptimal decisions is the failure of introspection. While people can usually describe the information they have considered to arrive at a decision for a specified outcome, they can rarely articulate the process they used to make the decision. Thus, this paper proposes the use of multi-criteria decision making approach and tests a model using the TOPSIS approach to tackle the processes associated with introspection. The results find that TOPSIS is able to use a set of criteria to help students systematically and rigorously choose a suitable course of study. This research is useful for potential tertiary students, education providers, education agencies and recruitment officers.